Revizija direktive o pravicah delničarjev - Direktiva (EU) 2017/828 Evropskega parlamenta in Sveta z dne 17. maja 2017 o spremembi Direktive 2007/36/ES glede spodbujanja dolgoročnega sodelovanja delničarjev - Kocbek, Marijan (Podjetje in delo, 2018)
Directive 2007/36/EC of the European Parliament and of the Council of 11 July 2007 on the exercise of certain rights of shareholders in listed companies was revised by Directive (EU) 2017/828 of the European Parliament and of the Council of 17 May 2017. The changes relate to encouraging the long-term participation of shareholders. The article discusses all four sets of issues governed by the amended directive, namely: identification of shareholders, providing information and facilitating the exercise of shareholders' rights, transparency of institutional investors, asset managers and voting advisors, shareholders' rights and information regarding the remuneration policy for directors, and transparency and the approval of business with related parties. A new amendment to the Companies Act (ZGD-1) will have to be adopted for the implementation of the directive in Slovenia at the latest by the middle of next year.
Keywords: direktive EU; novela ZGD-1; politika prejemkov direktorjev; pravice delničarjev